Intercultural communication: linguistic aspect (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article analyses one of the most important cross-cultural communication aspects – the linguistic aspect. Within verbal communication this aspect shows cultural and social individualities of addresser, using linguistic means of communication.
Keywords: aspects of cross-cultural communication; linguistic means; language divide; intercultural dialogue; cultural expression; language code; cultural and social context